Some uniqueness result on controllability for functional semilinear differential equations in Fréchet spaces - Arara, A.; Benchohra, M.; Ouahab, A. (Нелінійні коливання, 2003)
In this paper, a recent nonlinear alternative for contraction maps in Frechet spaces, due to Frigon and ´
Granas, is combined with semigroups theory and used to investigate the controllability of some classes of
semilinear functional and neutral functional differential equations in Banach spaces on the semiinfinite
interval. Дослiджується керованiсть для деяких класiв напiвлiнiйних функцiональних i нейтральних функцiонально-диференцiальних рiвнянь у банахових просторах на напiвобмеженому iнтервалi за допомогою теорiї напiвгруп, а також нещодавно отриманої Фрiгоном i Гранасом нелiнiйної альтернативи для стискаючих вiдображень у просторах Фреше.